THE POSITION OF IRAQI LAW ON THE EFFECT OF THE CRIMINAL RULING ON THE JOB ASSOCIATION RELATED TO THE RULING ISSUED IN A FELONY AND THE RULING FOR A MISDEMEANOR INVOLVING DISHONOR - Jasim Mohmmed Lafta; Hasanain Salim Hammood (Galaxy International Interdisciplinary Research Journal, 2024)
The research aims to explain the impact that a penal ruling can cause on the public job, as a penal ruling is the decision issued by a body entrusted by law with the task of adjudicating a dispute whenever it resolves disputes that have arisen over a specific legal status after inviting its parties to express their opinion on it, where the collection is done. He between the objective and formal criteria in determining the ruling by the authority that issues it, which is the court, and pointed out the dispute that could arise around a specific legal center and the topic that it addresses, which is resolving all or part of the dispute. The research is based on the basic hypothesis that the penal ruling has a positive impact on the public function in Iraqi legislation. The descriptive and analytical approach was relied upon when writing this research by defining the topic to be researched and describing the topic through the available information. The research reached a set of conclusions, the most important of which was that the penal ruling is a written decision issued by the public authority represented by the judiciary in the dispute presented before it with the aim of respecting the law and giving everyone his right. This ruling also affects the public function, which is described as the relationship that links a group of people. They are public employees and the state in which they work, and this relationship is regulated in accordance with the relevant laws to achieve the public good.